IDENTIFICATION ACTIVE POCKMARKS USING THE COMBINATION OF SIDE SCAN SONAR AND SUB-BOTTOM PROFILER - Riyatna, Rifki Ade (Journal of Marine-Earth Science and Technology, 2022)
It should be suitable for direct inclusion in abstracting services and should not normally be more than 300 words. Geohazards assessments are important before any engineering activity as they could block facilities and cause millions of dollars in losses. Pockmark as geohazards is often observed on the seabed with various amounts, especially on the clayey seabed sediments. Pockmarks indicate that the gas escapes from below the seabed. Pockmark may cause the jack-up rig to be slipped, pipeline free-span, and even blow out while drilling if it has a gas trap below. Side scan sonar and sub-bottom profiler as the geophysical method using acoustic wave can be used to investigate the active pockmarks. By using these two datasets, the distribution of active and inactive pockmarks can be achieved properly. So that hazards that may occur in engineering activities in the future can be prevented.